2018
DOI: 10.1038/s41598-018-24864-4
|View full text |Cite
|
Sign up to set email alerts
|

Ridge-furrow with plastic film and straw mulch increases water availability and wheat production on the Loess Plateau

Abstract: Mulching is critical for increasing water availability and hence winter wheat production in dryland farming systems. A two-year study was conducted to assess the effects of mulches on soil water storage (SWS), temperature, water use efficiency (WUE) and yields of winter wheat on the Loess Plateau. Four treatments were examined: conventional flat planting (CK), straw mulch (FPS), transparent plastic film mulch (FPP) and ridge-furrow with plastic film-mulched ridge and straw-mulched furrow (RFPS). Compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 57 publications
1
9
1
Order By: Relevance
“…Our result findings can be explained by the enhanced soil biological activity of the additive decomposer (Zhao et al 2016;Siczek et al 2018) and the optimal soil moisture and temperature condition under FM S tillage (Potthoff et al 2008;Gan et al 2013;Liu et al 2018). Moreover, our results indicated that the fast decomposition period of the buried maize straw lasted for 120 days, with a much lower residual mass rate under T1 than that under T2, which was much longer than the finding in an anaerobic field incubation test of buried wheat straw reported by Wang (2015).…”
Section: Straw Decomposition and Straw C And N Release As Affected Bysupporting
confidence: 57%
See 3 more Smart Citations
“…Our result findings can be explained by the enhanced soil biological activity of the additive decomposer (Zhao et al 2016;Siczek et al 2018) and the optimal soil moisture and temperature condition under FM S tillage (Potthoff et al 2008;Gan et al 2013;Liu et al 2018). Moreover, our results indicated that the fast decomposition period of the buried maize straw lasted for 120 days, with a much lower residual mass rate under T1 than that under T2, which was much longer than the finding in an anaerobic field incubation test of buried wheat straw reported by Wang (2015).…”
Section: Straw Decomposition and Straw C And N Release As Affected Bysupporting
confidence: 57%
“…Furthermore, SOC and SON responses to straw incorporation widely vary and are site-specific, largely contributing to the complex interactions between the quantity and quality of incorporated straw and native SOC under diverse management practices (Wang 2015). In our study, we found that K S , K C , and K N were significantly negatively correlated with initial SOC and SON, particularly in the presence of a straw decomposer both in the direct field incubation test and in the 3 years of field experiment; this resulted in a considerable amount of liberated straw C and N and high SOC and SON accumulation, probably because of the following reasons: First, addition of a decomposer enhanced the overall soil microbial activities in conjunction with the increased soil hydrothermal conditions under the FM tillage, resulting in rapid decomposition of the buried maize straw thus releasing additional nitrogen that gradually adjusted the straw and soil C/N ratio and favorably facilitated additional straw decomposition and straw C and N release (Li et al 2006;Jiang and Li 2015;Tang et al 2016;Liu et al 2018). Second, the addition of the decomposer might have offset some negative effects caused by the initial straw and soil chemical composition and the unfavorable soil moisture and temperature conditions during the early stages of straw decomposition through the multilateral reaction among them, synergistically enhancing the buried straw decomposition and C and N release, which was similar to the finding in the maize straw incubation reported by Qin et al (2015).…”
Section: Relationship Correlating Straw Decomposition and Straw C Andmentioning
confidence: 99%
See 2 more Smart Citations
“…One is the ridge mulched by the plastic film as the runoff area, and the other is the furrow, which acts in the planting area (Ren et al 2016a). The greatest advantage of RFFM is that it can effectively improve the temperature and moisture of topsoil, increase water use efficiency, soil nitrate, and organic carbon, and consequently increase crop yields of wheat (Liu et al 2018), maize (Wang et al 2018) and winter oilseed rape (Gu et al 2016) in the practice of agricultural production.Good soil environment, which is the basis for plant growth and development, can support sufficient water, fertilizer, gas, and heat for plants (Mimura…”
mentioning
confidence: 99%